2019
DOI: 10.1159/000496977
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypertension and the Risk of Parkinson’s Disease: A Meta-Analysis of Analytical Studies

Abstract: Background: The results of analytical studies show that the association between hypertension and the risk of Parkinson’s disease (PD) remains controversial. Method: We searched studies related to the association between hypertension and the risk of PD. We pooled the ORs and risk ratios (RRs) with 95% confidence interval (CI) with random effects model and conducted meta-regression to explore potential sources of heterogeneity. Publication bias was estimated by Egger’s test and the funnel plot. Results: Twenty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 36 publications
0
43
1
Order By: Relevance
“…Hypertension may damage blood vessels in basal ganglia that contain striatum and substantia nigra. A meta-analysis study also reported that hypertension might increase the risk of PD [23]. Another meta-analysis also reported a significant association of depression with a subsequent risk of PD [24].…”
Section: Discussionmentioning
confidence: 90%
“…Hypertension may damage blood vessels in basal ganglia that contain striatum and substantia nigra. A meta-analysis study also reported that hypertension might increase the risk of PD [23]. Another meta-analysis also reported a significant association of depression with a subsequent risk of PD [24].…”
Section: Discussionmentioning
confidence: 90%
“…The etiologic link between hypertension and PD has been debated 9 , with studies showing divergent results 10 , 11 . The neurodegenerative effect is postulated to be caused by vasculopathy leading to strategic infarcts that could affect dopaminergic cells and disrupt neuronal connections 12 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the expenditures on the treatment and prevention of hypertension are enormous; as reported, the US spent an estimated $51.2 billion from 2012 to 2013 [3]. Hypertension is one of the most common chronic diseases and a major risk factor for disease burden in the world [4], meanwhile it could increase the risk of stroke, cardiovascular disease, kidney failure, dementia, and Parkinson’s disease and so on [5,6,7,8,9]. In view of the huge disease burden of hypertension, the American College of Cardiology (ACC) and American Heart Association (AHA) adjusted the diagnostic criteria for hypertension to 130/80 mmHg in 2017 [10].…”
Section: Introductionmentioning
confidence: 99%